Talking to the people that really matter about their participation in pandemic clinical research: A qualitative study in four European countries. (27th September 2017) - Gobat, Nina H.; Gal, Micaela; Butler, Christopher C.; Webb, Steve A.R.; Francis, Nicholas A.; Stanton, Helen; Anthierens, Sibyl; Bastiaens, Hilde; Godycki‐ćwirko, Maciek; Kowalczyk, Anna; Pons‐Vigués, Mariona; Pujol‐Ribera, Enriqueta; et al.
Abstract: Background: Pandemics of new and emerging infectious diseases are unpredictable, recurrent events that rapidly threaten global health and security. We aimed to identify public views regarding provision of information and consent to participate in primary and critical care clinical research during a future influenza‐like illness pandemic. Methods: Descriptive‐interpretive qualitative study, using focus groups (n = 10) and semi‐structured interviews (n = 16), with 80 members of the public (>18 years) in Belgium, Spain, Poland and the UK. Local qualitative researchers followed a scenario‐based topic guide to collect data. Data were transcribed verbatim, translated into English and subject to framework analysis. Results: Public understandings of pandemics were shaped by personal factors (illness during the previous H1N1 pandemic, experience of life‐threatening illness) and social factors (historical references, media, public health information). Informants appreciated safeguards provided by ethically robust research procedures, but current enrolment procedures were seen as a barrier. They proposed simplified enrolment processes for higher risk research and consent waiver for certain types of low‐risk research. Decision making about research participation was influenced by contextual, research and personal factors. Informants generally either carefully weighed up various approaches to research participation or responded instinctively. They supported the principle of using routinely collected, anonymized clinical biological samples for research without explicit consent, but regarded this as less acceptable if researchers were motivated primarily by commercial gain. Conclusions: This bottom‐up approach to ascertaining public views on pandemic clinical research has identified support for more proportionate research protection procedures for publically funded, low‐risk studies.